Left Vertebral Artery Origin from the Thyrocervical Trunk: A Unique Vascular Variant - Strub, W.M.; Leach, J.L.; Tomsick, T.A. (American Journal of Neuroradiology, 2006)
SUMMARY: The vertebral artery normally arises from the subclavian artery, and variations in its origin have been described. We describe a unique case of the left vertebral artery arising from the thyrocervical trunk.